Treatment with a Substance P Receptor Antagonist Is Neuroprotective in the Intrastriatal 6-Hydroxydopamine Model of Early Parkinson's Disease - Thornton, Emma; Vink, Robert (PLOS ONE, 2012)
Neuroinflammation and blood brain barrier (BBB) dysfunction have been implicated in the pathogenesis of Parkinson's disease (PD). The neuropeptide substance P (SP) is an important mediator of both neuroinflammation and BBB dysfunction through its NK1 receptor in a process known as neurogenic inflammation. Increased SP content has previously been reported following 6-OHDA treatment in vitro, with the levels of SP correlating with cell death. The present study used an in vivo 6-OHDA lesion model to determine if dopaminergic degeneration was associated with increased SP in the substantia nigra and whether this degeneration could be prevented by using a SP, NK1 receptor antagonist. Unilateral, intrastriatal 6-OHDA lesions were induced and SP (10 µg/2 µL) or the NK1 receptor antagonists, N-acetyl-L-tryptophan (2 µL at 50 nM) or L-333,060 (2 µL at 100 nM), administered immediately after the neurotoxin. Nigral SP content was then determined using immunohistochemical and ELISA methods, neuroinflammation and barrier integrity was assessed using Iba-1, ED-1, GFAP and albumin immunohistochemistry, while dopaminergic cell loss was assessed with tyrosine hydroxylase immunohistochemistry. Motor function in all animals was assessed using the rotarod task. Intrastriatal 6-OHDA lesioning produced an early and sustained increase in ipsilateral nigral SP content, along with a breakdown of the BBB and activation of microglia and astrocytes. Further exacerbation of SP levels accelerated disease progression, whereas NK1 receptor antagonist treatment protected dopaminergic neurons, preserved barrier integrity, reduced neuroinflammation and significantly improved motor function. We propose that neurogenic inflammation contributes to dopaminergic degeneration in early experimental PD and demonstrate that an NK1 receptor antagonist may represent a novel neuroprotective therapy.